Analysis of The Factors Affecting The Compliance of Internship Dentist in The Implementation of Precaution Standards at Dentis't Hospital IIK Bhakti Wiyata Kediri - Cahyadinata, Indra; Indasah, Indasah; Siyoto, Sandu (Journal for Research in Public Health, 2019)
Dental health personnel in carrying out daily care can not be separated from contact with saliva and blood which can be an intermediary in the spread of cross infection. Cross infection is common in medical treatment procedures including dental and oral care. Prevention of cross infection needs to be done to avoid transmission of disease from medical procedures to patients and dental health workers. The purpose of this study was to determine the factors that influence the compliance of the dentist Koas to the application of the Precaution Standard at RSGM IIK BW Kediri. The method in this study was observational descriptive with cross-sectional design. The number of samples is 67 Koas dentists using the Slovin formula. The tools and materials used in the research are check list sheets and stationery. The data processing in this study uses the SPSS program by using a binary logistic test. The results of this study indicate that from several factors that influence the compliance of dentist councils in applying the precaution standard at RSGM IIK BW Kediri is a knowledge factor of p = 0.010 (<0.005), supervision is p = 0.003 (<0.005), and the availability of infrastructure is p = 0.006 (<0.005) with supervisory variables which are the variables that have the most individual influence compared to the other variables. Thus in drawing the conclusion that the level of knowledge, supervision and facilities and infrastructure is a factor that influences the compliance of dentists in implementing the implementation of precaution standards that have been set for prevention of cross infection.